Combined analysis of transcriptome and metabolome reveals that sugar, lipid, and phenylpropane metabolism are essential for male fertility in temperature-induced male sterile rice - Sun, Yujun; Fu, Ming; Ang, Yina; Zhu, Lan; Wei, Linan; He, Ying; Zeng, Hanlai (Frontiers in Plant Science, 2022)
Photoperiod- and thermo-sensitive genic male sterility (PTGMS) rice is a vital germplasm resources of two-line hybrid rice, and light and temperature strictly control their fertility changes. The variable environmental conditions bring huge risks to the two-series hybrid seed production process; therefore, explaining the regulatory mechanism of male fertility in PTGMS rice is an essential prerequisite to ensuring food security production. A group of near-isogenic lines (NILs) of PTGMS rice material unique to the research group was used for this study; they have the same genetic background and regulate male fertility by responding to different temperature changes. Transcriptomic analysis revealed that 315 up-regulated genes and 391 down-regulated genes regulated male fertility in response to temperature changes; enrichment analysis of these 706 DEGs revealed that they were mainly characterized in the metabolic pathways of sugar, lipid and phenylpropanoid. Phenotypic analysis revealed that lack of starch accumulated in sterile pollen grains induced by high temperature, with an abnormal exine development and lack of inner. And the defective processes of sporopollenin synthesis, sporopollenin transport and pollen wall formation in sterile anthers were verified by qPCR. Targeted metabolomics analysis revealed that most lipids (phospholipids, sphingolipids and fatty acids) and flavonoids (flavones and flavanones) were up-regulated in fertile anthers and involved in pollen wall development and male fertility formation; while lignin G monolignol and C-type lignin were the major contributors in pollen wall development. The coding genes for Trehalose 6-phosphate phosphatase, Beta-1,3-glucanase, Phospholipase D and 4-coumarate-CoA ligase are considered essential regulators in the process of male fertility formation. In conclusion, our results indicated that the expression of critical genes and accumulation of metabolites in the metabolic of sugar, lipid and phenylpropanoid are essential for male fertility formation. The results provide new insights to address the negative effects of environment variation on two-lines hybrid rice production.